From mono- to multiculturalism. Towards the development of intercultural competence for Chinese ELE students through a MOOC course - Chen, Zhi; Chen, Danna; Jia, Mengzhen (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Intercultural competence is a fundamental skill for anyone in an increasingly globalized world, especially for foreign language learners. With the widespread use of the Internet, teaching methods should be recalibrated to meet the needs of a new social order. This article seeks to explore the effectiveness of the course “Introduction to Chinese festivals and their cultural connotations” taught based on a B-learning model (MOOC + face-to-face classes) in a Chinese university. The establishment of a new ecosystem for the teaching of interculturality between China and the Hispanic world is proposed, in which the three levels (the technical, cognitive and axiological) intertwine and reinforce each other to create a closed loop.